The Fostering and Developing Students' Entrepreneurial Intentions Through Entrepreneurship Curriculum and Self-Efficacy: Evidence From Regression Analysis - Prastiko, Mufti Nawang; Mustiningsih, Mustiningsih; Sumarsono, Raden Bambang (JMK (Jurnal Manajemen dan Kewirausahaan), 2024)
The objective of this study is to identify and determine the level and impact of the entrepreneurship curriculum and self-efficacy on students' entrepreneurial intentions. This research employs a quantitative approach, utilizing descriptive analysis and multiple linear regression with partial t-tests and simultaneous f-tests. The study involves a sample of 100 students from faculties of Mathematics and Science (FMIPA), Engineering (FT), Education (FIP), and Letters (FS) at Universitas Negeri Malang. The sample size was determined using quota sampling, which provides researchers the flexibility to decide the number of participants. First, the entrepreneurship curriculum, manifested through entrepreneurship education, was rated as "Very Good". Second, students' self-efficacy was classified as "Very Good". Third, students' entrepreneurial intentions were classified as "Good". Fourth, the entrepreneurship curriculum variable significantly influences students' entrepreneurial intentions. Fifth, the self-efficacy variable significantly influences students' entrepreneurial intentions. Sixth, the simultaneous testing of the entrepreneurship curriculum and self-efficacy variables revealed a significant combined effect on students' entrepreneurial intentions.